PENGUJIAN ANOMALI PASAR MONDAY EFFECT, WEEKEND EFFECT, ROGALSKI EFFECT DI BURSA EFEK INDONESIA - Ranita Ramadhani; Imam Subekti (Jurnal Ilmiah Mahasiswa FEB, 2014)
ABSTRACT This research aims to investigate anomaly Monday Effect, Weekend Effect, and Rogalski Effect by using stocks in the LQ45 index and in the JII index on 2011, 2012, and 2013. The research use non-parametric statistic test method. The result show that Anomaly Monday Effect does exist in Indonesia Stock Exchange (BEI) whereas Anomaly Weekend Effect does exist partially, that is Friday-Monday and Friday-Thursday. Then, the result of Rogalski Effect find that Rogalski Effect in January only exist in the LQ45 index on 2013 but does not exist in the JII index on 2013 and in the LQ45 and JII index on 2011 and 2012.  Keywords: Market Eficiency, Anomaly Monday Effect, Anomaly Weekend Effect, Anomaly Rogalski Effect